Cost-effectiveness analysis of combining lenalidomide with R-CHOP for treating diffuse large B-cell lymphoma in China - Li, Rongqi; Zeng, Yuhan; Chen, Yizhang; Ye, Zhongjiang; Chen, Chuang; Yang, Jianhui; Fu, Jing; Zhou, Tao; Jiang, Danna; Qin, Sunting; Ye, Haige; Zhou, Ziye; et al. (Frontiers in Pharmacology, 2024)
Background: Lenalidomide is a thalidomide analog that has immunomodulatory and anti-angiogenic properties. The ECOC-ACRIN E1412 Phase II trial demonstrated that lenalidomide, when combined with rituximab, cyclophosphamide, adriamycin, oncovin, and prednisone (R-CHOP), extended survival in diffuse large B-cell lymphoma (DLBCL) patients. This study aimed to evaluate the cost-effectiveness of combining lenalidomide with R-CHOP (R2-CHOP) versus R-CHOP alone as the initial treatment for DLBCL from the perspective of the Chinese health system.We developed a 5-year partitioned survival model to compare the costeffectiveness of R2-CHOP versus R-CHOP alone. The clinical data came from the ECOG-ACRIN E1412 clinical trial. The costs of drugs and examinations were obtained from publicly available Chinese medical databases and literature. Model robustness was assessed by sensitivity analysis and scenario analysis. And subgroup analysis was also performed. Key outcomes include total cost, quality-adjusted life years, and the incremental cost-effectiveness ratio.Results: Over a 5-year time horizon, the basic analysis results of the partitioned survival model showed that the ICER of $35,159.06 per QALY for R2-CHOP compared to R-CHOP. Deterministic sensitivity analysis revealed that the price of lenalidomide is the main factor affecting cost-effectiveness. Probabilistic sensitivity analysis indicated a 67.9% chance of lenalidomide plus R-CHOP being cost-effective at the willingness-to-pay threshold, compared to R-CHOP alone. Scenario analysis showed R2-CHOP scenarios to be cost-effective for 10 to 30 years. And subgroup analysis showed that treating activated B cell-like type DLBCL with R2-CHOP was more costeffective.In the Chinese healthcare system, R2-CHOP is a cost-effective approach for DLBCL compared to R-CHOP, but the costs of lenalidomide and rituximab warrant attention.